Social Accountability 3.0: Engaging Citizens to Increase Systemic Responsiveness. Background Paper - Guerzovich, Florencia; Aston, Tom (Grupo Politeia, ESAG, UDESC and act4delivery, 2024)
Social accountability has become increasingly important to development programming since the 2004 World Development Report spearheaded its first generation of programming. In 2016, Thomas Carothers synthesized global experts’ perspectives on what became known as the second generation. With an evolving global context, new research and evaluations and tacit knowledge on how those assumptions played out in practice, the time is ripe for asking what the evidence since 2004 can tell us about what the social accountability’s next generation might look like? This meta-analysis takes stock of that knowledge through a systems lens and presents a possible “social accountability 3.0.” It draws on a database of 157 cases of initiatives implemented by different civil society organizations around the world and the lived experience of practitioners. Scholarly debates present practitioners’ options in binary terms, contrasting 1.0 minimalist and 2.0 maximalist options. The review finds that this binary is inaccurate and misleading; it masks practitioners’ diverse interpretations of 2.0 and range of feasibility considerations. Instead, work in the last decade looks more like a mosaic. By opening the analysis to the broader range of evidence, and reflecting more critically on scholars’ assumptions, a more adaptable middle path for social accountability 3.0 emerges. Its key outcomes include contributing to systemic responsiveness and an operational mechanism to rework the social contract.

Disentangling Government Responses: How Do We Know When Accountability Work is Gaining Traction? - Fox, Jonathan; Halloran, Brendan; Fölscher, Alta; McGee, Rosie (Working Paper, 2024)
Advocacy for public accountability aims to produce certain reactions from government officials or service providers. However, the reactions can be many and diverse, and it is not always clear to advocates how to interpret them and decide on next steps—whether to intensify efforts or back off; continue the same strategy or make adjustments. This paper presents a framework to help accountability advocates and practitioners interpret government reactions to their efforts and move forward appropriately. The framework arises from learning and reflection in the context of the International Budget Partnership (IBP)’s Strengthening Public Accountability with Results and Knowledge (SPARK) program. SPARK seeks to bolster the collective agency of marginalized communities and coalitions to advance democratic and equitable fiscal governance systems that channel public resources to services that address the priority needs of these historically excluded groups. The paper: · unpacks the broad umbrella category of government responses to citizen-led accountability initiatives, discerning within it three overlapping categories of responses, responsiveness, and accountable responsiveness (RRA), and pinpointing what distinguishes them; · maps out the public financial management (PFM) system as the critical conduit for any public service to progress from non-response through these three categories, reflecting the terrain and priorities of the SPARK program and IBP more broadly. Looking at RRA in the context of this PFM map offers key insights for the twin tasks of tracing and unblocking bottlenecks in resource management systems that hinder responsiveness and accountability, as well as demanding specific reforms that make the fiscal governance system more open to citizen engagement; and · discusses how the RRA framework can be used to take stock of partial or incremental responses and assess whether change is moving towards accountable governance, by reference to the SPARK program and other IBP efforts. The RRA framework supports accountability-claiming practice by facilitating close attention to the actions of and influences on key government stakeholders, careful interpretation of these, and consequential adjustments to advocacy strategies. Its implications for monitoring, evaluating, and learning (MEL) from practice are also significant. MEL has been evolving in the accountability field in line with the thinking and practical challenges behind the development of the RRA framework. The framework adds to a range of emerging approaches that support the application theories of change, evidence-based adaptive programming, and politically aware systems thinking in the complex task of building accountable responsiveness towards constituencies historically excluded from public goods and services, and ultimately equitable development outcomes from an intersectional perspective.
Keywords: Development studies; Public policy; Social policy